2007
DOI: 10.1038/nbt1288
|View full text |Cite
|
Sign up to set email alerts
|

An anti-infective peptide that selectively modulates the innate immune response

Abstract: We show that an innate defense-regulator peptide (IDR-1) was protective in mouse models of infection with important Gram-positive and Gram-negative pathogens, including methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus and Salmonella enterica serovar Typhimurium. When given from 48 h before to 6 h after infection, the peptide was effective by both local and systemic administration. Because protection by IDR-1 was prevented by in vivo depletion of monocytes and macrophages, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
454
4
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(490 citation statements)
references
References 28 publications
28
454
4
4
Order By: Relevance
“…This effect might be related to its tissue distribution and pharmacokinetics, which have not yet been investigated. Alternatively it might have a mechanism similar to some AMPs, which can act indirectly through modulation of the host immune system (45). Thus, the increasing efficacy of 6c with longer delays between doses might be associated with the priming of an immune response, which is then augmented by the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…This effect might be related to its tissue distribution and pharmacokinetics, which have not yet been investigated. Alternatively it might have a mechanism similar to some AMPs, which can act indirectly through modulation of the host immune system (45). Thus, the increasing efficacy of 6c with longer delays between doses might be associated with the priming of an immune response, which is then augmented by the second dose.…”
Section: Discussionmentioning
confidence: 99%
“…HDPs are promising new agents [6,14,15,19] that, owing to their unique immunomodulatory mechanisms of action, are less likely to induce bacterial resistance than are conventional antibiotics [14,15]. Moreover, HDPs can also modulate cytokine production to control the inflammatory response [14,15,19,28,38] and thereby may reduce the risk of developing inflammatory osteolysis. IDR-1018 is one of the most attractive of the HDPs [1,26,30,32,37,39,42].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, evidence has accumulated that the antiinfective effects of HDPs are also the result of their immunomodulatory properties such as upregulation of expression of chemokines that, in turn, recruit and activate host immune cells [6,14,15,19,28,38]. HDPs can also modulate production of pro-and antiinflammatory cytokines to control the inflammatory response [14,15,19,28,38] and can inhibit osteoclast differentiation [20,40] and thereby potentially can reduce inflammatory osteolysis and the lethal consequences of septic shock. As a result of their unique immunomodulatory mechanisms of action, HDPs are also less likely to induce bacterial resistance than are conventional antibiotics [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, it has been shown that several IDRs suppress proinflammatory responses modulating M1eM2 macrophage differentiation (Pena et al, 2013), suppressing potentially harmful excessive inflammatory responses (Scott et al, 2007) and offering protection by enhancing the innate immune defences of the host, thus suggesting again that whey-derived peptides could be used as natural IDRs.…”
Section: Pes-1 Fraction Can Promote Regulatory T Cell Responsesmentioning
confidence: 74%